Maternal immune activation induces sex-dependent behavioral differences in a rat model of schizophrenia - Liu, Yunxia; Hang, Xiaoyi; Zhang, Yijie; Fang, Yilin; Yuan, Shanfang; Zhang, Yi; Wu, Bin; Kong, Yan; Kuang, Zihe; Sun, Wenjun (Frontiers in Psychiatry, 2024)
Background Maternal immune activation (MIA) is a mature means to construct a schizophrenia model. However, some preclinical studies have reported that a MIA-induced schizophrenia model seemed to have gender heterogeneity in behavioral phenotype. On the other hand, the MIA’s paradigms were diverse in different studies, and many details could affect the effect of MIA. To some extent, it is not credible and scientific to directly compare the gender differences of different MIA programs. Therefore, it is necessary to study whether the sex of the exposed offspring leads to behavioral differences on the premise of maintaining a consistent MIA mode. Methods An animal model of schizophrenia was established by the administration of 10 mg/kg Poly (I: C) when dams were on day 9 of gestation. Then, a number of female and male offspring completed a series of behavioral tests during postnatal days 61–75. Results Compared with the female control group (n = 14), female MIA offspring (n = 12) showed a longer movement distance (d = 1.07, p < 0.05) and higher average speed (d = 1.08, p < 0.05) in the open field test (OFT). In the Y maze test, the percentage of entering the novel arm of female MIA offspring was lower (d = 0.92, p < 0.05). Compared with the male control group (n = 14), male MIA offspring (n = 13) displayed less movement distance (d = 0.93, p < 0.05) and a lower average speed (d = 0.94, p < 0.05) in the OFT. In the Y maze test, the proportion of exploration time in the novel arm of male MIA offspring was lower (d = 0.96, p < 0.05). In the EPM, male MIA offspring showed less time (d = 0.85, p < 0.05) and a lower percentage of time spent in the open arms (d = 0.85, p < 0.05). Male MIA offspring also had a lower PPI index (76 dB + 120 dB, d = 0.81, p < 0.05; 80 dB + 120 dB, d = 1.45, p < 0.01). Conclusions Our results showed that the behavioral phenotypes induced by prenatal immune activation were highly dependent on the sex of the offspring.